Particle Ratios at the Cern P? P Collider - Liang, Thow Yick (Institutional Knowledge at Singapore Management University, 1984)
By applying Chao-Yang statistics to multiplicities of different particles in pp collisions, we obtain good quantitative agreement with the data obtained from CERN ISR experiments. What is especially significant in this work is that the ? / p ratios are given correctly for all energies. Predictions for various particle ratios for p? p collisions are also calculated for confirmation by future experiments.